2022
DOI: 10.5115/acb.22.023
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of the groove of the inferior petrosal sinus: application to better understanding variations and surgery of the skull base

Abstract: Although adequate venous drainage from the cranium is imperative for maintaining normal intracranial pressure, the bony anatomy surrounding the inferior petrosal sinus and the potential for a compressive canal or tunnel has, to our knowledge, not been previously investigated. One hundred adult human skulls (200 sides) were observed and documented for the presence or absence of an inferior petrosal groove or canal. Measurements were made and a classification developed to help better understand their anatomy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Gupta et al studied 50 dry skulls and found that complete septation was found in 44% on the right side and 42% on the left side [24]. We recently published an anatomical study where the different septations of the jugular foramen were classified [2,25].…”
Section: Discussionmentioning
confidence: 99%
“…Gupta et al studied 50 dry skulls and found that complete septation was found in 44% on the right side and 42% on the left side [24]. We recently published an anatomical study where the different septations of the jugular foramen were classified [2,25].…”
Section: Discussionmentioning
confidence: 99%
“…OC resection extended to HC in patients with an anteriorly located HC may increase the risk of CVJ instability [ 16 ]. JF is a canal that contains the jugular bulb and cranial nerves including the glossopharyngeal (CN IX), vagus (CN X), and accessory nerve (CN XI) [ 21 , 22 ]. The JF should be avoided during an OC resection because it may cause damage to neurovascular structures that pass through it [ 19 ].…”
Section: Introductionmentioning
confidence: 99%